The Halal Tourism Preferences: The Role of Brand Awareness, Attitudes, and Social Norms Among Muslim and Non-Muslim Travelers - Setyaningsih, Ira; Kurniatanty, Isma; Ovianti, Dita; Intan Maharani, Novia (Journal of Industrial Engineering and Halal Industries, 2024)
This research focuses on the influence of brand awareness, attitudes, and social norms on the intentions of Muslim and non-Muslim tourists to visit Lombok as a Halal tourism destination. Lombok has been designated by the Indonesian government as a center for Islamic tourism, providing a complementary option to Bali’s Hindu cultural tourism. The study utilized the Theory of Planned Behavior and gathered data via an online survey involving 123 participants, 56 non-Muslims and 67 Muslims. The results indicated that Halal brand awareness and social norms did not significantly impact non-Muslim tourists' intentions to visit Lombok. At the same time, brand awareness also did not affect Muslim tourists. Attitudes were identified as the main factor influencing their willingness to visit. Interestingly, the R-squared values differed notably between the two groups, with the variables accounting for 58.1% of non-Muslim tourists' decisions but only 39.9% for Muslim tourists. This research offers new insights into Halal tourism from both Muslim and non-Muslim perspectives.